Моя незнакомая жизнь: роман / А. Полянская - Полянская Алла (Эксмо, 2014)
Экземпляры: аб. (20150224) / Инвентарный номер: 51429 / Цена: 70. 00. / Сис.шифр: Р2 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44